“Senam Kecerdasan” as a Psychological Intervention to Enhance Authentic Happiness: A Biopsychological and Islamic Perspective - Fuaturosida, Rika; Agung, Yusuf Ratu; Rochim, Edvin Eka Nur (Psikoislamika: Jurnal Psikologi Islam, 2025)
Globalization and rapid flow of information have profoundly impacted various aspects of life, including mental health. Amid social pressures and the demands of modern life, many individuals are experiencing a decline in authentic happiness (Clark Senik, 2011). One consequence of this is an increased reliance on counselors or professional help as the primary solution to address psychological issues. While this reliance may be helpful in the short term, it can hinder emotional independence and reduce an individual's ability to build psychological resilience on their own. Therefore, an alternative approach is needed that can strengthen mental well-being in a holistic and sustainable manner. This study aims to explore the effects of intelligence exercises on enhancing authentic happiness among individuals who have completed counseling. Using a one-group pretest-posttest design, this study examined seven counseling participants from UIN Maulana Malik Ibrahim Malang who voluntarily completed the intelligence exercise intervention. The measurement tool used was the Authentic Happiness Scale, adapted from (R. Sherlywati, 2015) research. Data analysis was conducted using nonparametric tests with the Wilcoxon Signed Ranks Test to assess significant changes in authentic happiness scores between the pretest and posttest measurements. The results showed an increase in authentic happiness scores after participants underwent the intelligence exercise program, with an average pretest score of 324.8571 and a posttest score of 338.7143 (p 0.05). The effect size calculation using Cohen's d yielded a value of 0.83 (large category). Through observation and interviews, positive changes were also detected in the subjects, including increased energy levels, reduced anxiety symptoms, and enhanced feelings of greater calmness and happiness. Islamic studies and biopsychological research also indicate that intelligence exercises, as a form of body and mind therapy, align with Islamic principles regarding the balance of soul and body. Intelligence exercises have significant effectiveness in enhancing authentic happiness. The practical implications of this study are that intelligence exercises can be widely applied in various settings, such as schools, workplaces, and communities, as a mental health promotion program. Additionally, this approach can reduce individuals' reliance on conventional therapy and encourage the development of emotional independence and sustainable psychological well-being. From a theoretical perspective, this research reinforces the importance of interventions based on physical and cognitive activities within a biopsychological framework and opens opportunities for integration with local or religious values, such as the Islamic perspective.Keywords: Intelligence Exercises; Authentic Happiness; Psychology; Biopsychology; Islam; Non-Parametric Testing